Neoplastic Spindle Cells Are an Independent Prognostic Factor in Pancreatic Cancer. Issue 5 (July 2015) - Takahashi, Kenjiro; Hisaka, Toru; Horiuchi, Hiroyuki; Ishikawa, Hiroto; Nakayama, Masamichi; Nakashima, Osamu; Kawahara, Akihiko; Kage, Masayoshi; Yano, Hirohisa; Akagi, Yoshito; Yonemoto, Koji; Kinoshita, Hisafumi; et al.
<x xml:space="preserve">Abstract</x> Objective Several reports showed that neoplastic spindle cells (NSCs) may be strongly involved in the invasion, metastasis, and poor prognosis, as well as in epithelial-mesenchymal transition (EMT). It has not yet been investigated that NSCs relate to the recurrence and prognosis in various cancers. Furthermore, NSCs participate in EMT in pancreatic cancer (PC) too. We clinicopathologically investigated the association between NSCs and the recurrence, prognosis, and EMT in PC. Methods We studied 68 PC patients. Cancer cells with a spindle or oval shape that do not exhibit luminal structures were defined as NSCs. We graded NSCs regarding to an area of NSCs at hematoxylin and eosin stain (NSC grade) and examined the participation in NSCs and EMT by immunohistostaining of snail antibody and E-cadherin antibody. Results In multivariate analysis, NSC grade was an independent risk factor for disease-free survival and overall survival. This was independent of TNM stage and histological grade. Neoplastic spindle cells were related to EMT pattern in immunohistostaining significantly. Conclusions Neoplastic spindle cell grade significantly related to the recurrence and prognosis of PC. The NSC grade assessment can be not only performed inexpensively and conveniently, but also used to guide future individualized therapeutic approaches. Furthermore, NSCs were found to relate to EMT profoundly.